Stakeholder Role Analysis in Managing the Special Purpose Forest Areas (KHDTK) of Mungku Baru, Central Kalimantan, Indonesia - Nanang Hanafi; Ahmad Jauhari; Gusti Muhammad Hatta; Hafizianor Hafizianor (Journal of The Community Development in Asia, 2025)
The change in status of forest areas to Special Purpose Forest Areas (KHDTK) aims to optimize forest resource management to support sustainability and sustainable use. KHDTK Mungku Baru is one example of an area managed by the local government and universities, but it faces various challenges, especially conflicts of interest between stakeholders. This research aims to analyze the role of stakeholders in managing KHDTK Mungku Baru and understand the interests and influence of each party in the management process. Data were collected through in-depth interviews with various parties involved, such as local governments, academics, NGOs, and the surrounding community. The results of the study indicate that stakeholders in the management of KHDTK Mungku Baru can be categorized into four groups based on their level of influence and interests: key players, context setters, subjects, and crowd. Local communities have high interests but low influence in the management of KHDTK, thus requiring a more effective empowerment approach. Meanwhile, local governments and academic institutions, as key players, play a major role in decision-making and policy implementation. To optimize the management of KHDTK Mungku Baru, a collaborative strategy that actively involves all stakeholders is needed.